Utilization of YouTube Media in Training Maharah Istima' at Muhammadiyah Sidoarjo High School: Pemanfaatan Media Youtube Dalam Melatih Maharah Istima’ Di SMA Muhammadiyah Sidoarjo - Masdawati, Lintang Jahwani; Arifin, Moch. Bahak Udin By (Universitas Pendidikan Muhammadiyah Sorong, 2024)
In the world of education, learning innovations continue to be pursued in order to adapt to the development of science. YouTube is one of the social media platforms that can be used as learning media. There are still few studies that utilize YouTube as an Arabic learning media to train students to become active listeners instead of passive ones. This study aims to find out the entire learning process and the impact of YouTube media utilization in training maharah istima' of class XI-C students at Muhammadiyah 3 Tulangan Sidoarjo Senior High School. This research used qualitative method with descriptive approach. Data collection techniques were conducted through observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model with three stages in the form of data reduction, data presentation and conclusion drawing. The Results showed that the utilization of YouTube media in training maharah istima' is feasible to be reused in continuing the Arabic language learning process thus Arabic language learning can adjust to the development of science. YouTube is used as a measuring tool for students' ability to master in Arabic which gives a positive impact.